TRANSLATION STUDIES IN THE AGE OF GLOBALIZATION: THEORY, PRACTICE, AND TECHNOLOGICAL TRANSFORMATION - Sahila Ibrahimova (THE USE OF MODERN DIGITAL TECHNOLOGIES IN LINGUISTICS AND FOREIGN LANGUAGE TEACHING. INTERNATIONAL SCIENTIFIC AND PRACTICAL CONFERENCE, 2026)
This article examines the development of translation studies as an interdisciplinary field influenced by linguistic, cultural, and technological factors. It explores key theoretical approaches, including equivalence theory, Skopos theory, and descriptive translation studies, highlighting their contributions to modern translation practices. The study emphasizes the importance of translation in intercultural communication, where linguistic competence must be complemented by cultural awareness. The paper also analyzes the impact of technological advancements such as machine translation, computer-assisted tools, and artificial intelligence. While these innovations have increased efficiency, they also raise concerns about quality, ethics, and the diminishing role of human translators. Furthermore, the article discusses the challenges faced in contemporary translation, including the loss of meaning, cultural differences, and technological dependence. It argues that despite automation, human translators remain indispensable for ensuring accuracy and cultural sensitivity. In conclusion, translation studies continues to evolve in response to globalization and technological progress. The integration of theoretical frameworks and practical applications is essential for addressing the complexities of modern translation. The study highlights the need for a balanced approach that combines human expertise with technological tools to enhance the effectiveness of translation in a globalized world.